1986
DOI: 10.1002/xrs.1300150212
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative electron probe microanalysis of carbon in binary carbides. I—principles and procedures

Abstract: Introductory investigations performed in order to make quantitative electron-probe microanalysis of very light elements such as boron, carbon, nitrogen or oxygen possible are described. The practical problems encountered in this kind of work are discussed in detail and, where possible, solutions are proposed. It is shown that with very light elements such as carbon it is no longer permitted to measure x-ray intensities at the position of the maximum of the emission peak as the shape of the carbon K a peak is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 11 publications
2
59
2
Order By: Relevance
“…Contrary to our previous studies on quantitative EPMA of carbon 1 and Boron 2 which were completed in one year and less than a year, respectively, the present work on Nitrogen has taken considerably more time. As a matter of fact the micro probe measurements were carried out over a period of approx.…”
Section: Introductionmentioning
confidence: 69%
“…Contrary to our previous studies on quantitative EPMA of carbon 1 and Boron 2 which were completed in one year and less than a year, respectively, the present work on Nitrogen has taken considerably more time. As a matter of fact the micro probe measurements were carried out over a period of approx.…”
Section: Introductionmentioning
confidence: 69%
“…The measurements were performed at 4, 6,8,10,12,15,20,25 and 30keV. In order to avoid excessive dead-time corrections for the metal lines (see Part I), the metals and carbon were measured separately.…”
Section: Methodsmentioning
confidence: 99%
“…the atomic number and the absorption corrections, the latter are likely to be responsible for the systematic deviations. Of course also the errors introduced by the fundamental parameters must be considered; Bastin and Heijligers [51] and Sevov et al [4] showed remarkable changes of the k'/k-values resulting from even small uncertainties of the mass absorption coeh'icients. [1].…”
Section: Primary Ionization Intensitiesmentioning
confidence: 99%